Transformasi Peran Guru Pendidikan Agama Islam dalam Menghadapi Ekosistem Pembelajaran Berbasis Artificial Intelligence - Muzawir Munawarsyah; Sonia Isna Suratin (Pascasarjana IAI Al-Khairat Pamekasan, 2026)
The development of Artificial Intelligence globally and nationally is transforming the learning ecosystem, requiring Islamic Religious Education teachers to adapt to pedagogical, ethical, and cultural changes to maintain the relevance of religious education. This study aims to analyze the transformation of the role of Islamic Religious Education teachers in facing the Artificial Intelligence-based learning ecosystem, by emphasizing their contribution to strengthening religious, humanistic, and religious moderation values ​​in the digital era. This study uses a qualitative approach with a literature review. Data sources come from various relevant scientific literature, including books, journal articles, proceedings, and national education policy documents that discuss Artificial Intelligence in education, particularly in the context of Islamic Religious Education learning. Data collection techniques are carried out through searching, collecting, and critical review of credible and up-to-date written sources. Data analysis is carried out by organizing, classifying, and synthesizing findings from various literature to obtain a comprehensive conceptual and thematic picture. Data validity is maintained through the selection of relevant, authoritative sources that are consistent with the focus of the study. The research findings indicate that the transformation of the role of Islamic Religious Education teachers involves a shift from transmitting knowledge to facilitating meaningful learning, reinforcing ethical digital literacy, and exemplifying the internalization of Islamic values ​​within a technological context. Artificial Intelligence has the potential to enhance learning effectiveness when coupled with teachers' pedagogical, spiritual, and critical competencies. The implications of this research emphasize its theoretical contribution to the development of a technology-adaptive Islamic Religious Education paradigm, as well as its practical contribution as a strategic reference for teachers and educational policymakers.